HIV-1 subtype C envelope characteristics associated with divergent rates of chronic disease progression. - Archary, D; Gordon, M; Green, T; Coovadia, H; Goulder, P; Ndung'u, T (2010)
BACKGROUND: HIV-1 envelope diversity remains a significant challenge for the development of an efficacious vaccine. The evolutionary forces that shape the diversity of envelope are incompletely understood. HIV-1 subtype C envelope in particular shows significant differences and unique characteristics compared to its subtype B counterpart. Here we applied the single genome sequencing strategy of plasma derived virus from a cohort of therapy naïve chronically infected individuals in order to study diversity, divergence patterns and envelope characteristics across the entire HIV-1 subtype C gp160 in 4 slow progressors and 4 progressors over an average of 19.5 months. RESULTS: Sequence analysis indicated that intra-patient nucleotide diversity within the entire envelope was higher in slow progressors, but did not reach statistical significance (p = 0.07). However, intra-patient nucleotide diversity was significantly higher in slow progressors compared to progressors in the C2 (p = 0.0006), V3 (p = 0.01) and C3 (p = 0.005) regions. Increased amino acid length and fewer potential N-linked glycosylation sites (PNGs) were observed in the V1-V4 in slow progressors compared to progressors (p = 0.009 and p = 0.02 respectively). Similarly, gp41 in the progressors was significantly longer and had fewer PNGs compared to slow progressors (p = 0.02 and p = 0.02 respectively). Positive selection hotspots mapped mainly to V1, C3, V4, C4 and gp41 in slow progressors, whereas hotspots mapped mainly to gp41 in progressors. Signature consensus sequence differences between the groups occurred mainly in gp41. CONCLUSIONS: These data suggest that separate regions of envelope are under differential selective forces, and that envelope evolution differs based on disease course. Differences between slow progressors and progressors may reflect differences in immunological pressure and immune evasion mechanisms. These data also indicate that the pattern of envelope evolution is an important correlate of disease progression in chronic HIV-1 subtype C infection.